2012
DOI: 10.1038/sc.2012.139
|View full text |Cite
|
Sign up to set email alerts
|

Increase in soluble CD95L during subacute phases after human spinal cord injury: a potential therapeutic target

Abstract: Study design: A pilot study measuring the levels of serum-soluble CD95 ligand (CD95L) in eight spinal cord-injured patients. Objectives: To determine the soluble concentration of CD95L in spinal cord injury (SCI) patients after trauma. Methods: We collected blood samples from eight patients with acute traumatic SCI. Soluble CD95L serum levels were determined using an enzyme-linked immunosorbent assay. American Spinal Injury Association (ASIA) was determined according to ASIA classification. The patients were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…According to the respective status of the database, different collections of serum samples have been analyzed to address the respective scientific issues. 8,9,[19][20][21][22][23][24] Assessment of the AIS grades took place at the admission as well as after 12 weeks in accordance with the International Standards for Neurological Classification of SCI (ISNCSCI). 25 The criterion for neurological remission was defined as positive conversion of AIS grades within 12 weeks after trauma.…”
Section: Methodsmentioning
confidence: 99%
“…According to the respective status of the database, different collections of serum samples have been analyzed to address the respective scientific issues. 8,9,[19][20][21][22][23][24] Assessment of the AIS grades took place at the admission as well as after 12 weeks in accordance with the International Standards for Neurological Classification of SCI (ISNCSCI). 25 The criterion for neurological remission was defined as positive conversion of AIS grades within 12 weeks after trauma.…”
Section: Methodsmentioning
confidence: 99%
“…This is supported by the fact that levels of sFas at 3 days are negatively correlated with troponin levels, ie the larger infarct the lower levels of sFas. Also, several studies measuring sFas and sFasL during the acute phase response to various diseases have found these markers to be unaltered or even reduced [228,229]. In this context it is noteworthy, that sFas/sFasL did not correlate with IL-6.…”
Section: Study IVmentioning
confidence: 81%
“…After binding, TNF triggers signal transduction pathways, including apoptosis and the nuclear factor kappa-light-chain-enhancer of activated B cells and JNK pathways. 10,11 Second, the upregulation of the DNA methyltransferase 3 (DNMT3) gene indicated that DNA methylation might contribute to spinal cord injury in DCS. DNMT is required for the establishment and maintenance of DNA methylation.…”
Section: Discussionmentioning
confidence: 99%